An efficient correlation-based storage location assignment heuristic for multi-block multi-aisle warehouses - Islam, Md. Saiful; Uddin, Md. Kutub (International Journal of Industrial Engineering and Management, 2024)
The most labor-intensive and time-consuming part of warehouse operations is order picking. This paper proposes a correlation-based storage location assignment (CBSLA) approach to minimize the travel distance of the picker in a picker-to-parts warehouse. At first, the proposed CBSLA approach forms some groups of stock-keeping units (SKUs) for different warehouse aisles. Then these groups of SKUs are assigned to the storage locations considering both the correlations between SKUs in a group and the correlation between groups of SKUs for efficient order picking. The effectiveness of the proposed method is measured for various warehouse configurations using simulation and compared with other well-known storage allocation methods. Article history: Received (May 6, 2023); Revised (March 21, 2024); Accepted (April 6, 2024); Published online (April 16,2024)